Implementation of Active Force Control to Reduce Vibration Displacement in Active Mass Damper during Seismic Activity - Salim, Mohd Azli; Noordin, Aminurrashid (ICOCI Publisher, 2011)

(untitled)
High structure in this world are using damper as a vibration controller device. The vibration control in a building is very important due to the public safety. In this study, Active Mass Damper (AMD) is used as a building’s structure and tested using Active Force Control (AFC) during the seismic activity. By using a software, two dimensional mathematical models and transfer function, stability of AMD and stability of AMD with AFC was identified, respectively. From the analysis, without AFC, the vibration displacement of AMD is slightly proportional due to amplitude and time. With AFC, the overshoot of the AMD system was reduced to 0% and the relationship between vibration displacement , amplitude and time was nonlinear for each others. For a conclusion, the AFC has a potential to reduce the relationship between vibration, amplitude and time and can gives AMD system more stable.